2017
DOI: 10.1186/s12932-017-0039-y
|View full text |Cite
|
Sign up to set email alerts
|

A survey of photogeochemistry

Abstract: The participation of sunlight in the natural chemistry of the earth is presented as a unique field of study, from historical observations to prospects for future inquiry. A compilation of known reactions shows the extent of light-driven interactions between naturally occurring components of land, air, and water, and provides the backdrop for an outline of the mechanisms of these phenomena. Catalyzed reactions, uncatalyzed reactions, direct processes, and indirect processes all operate in natural photochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 372 publications
(147 reference statements)
0
27
0
Order By: Relevance
“…phototrophic | mineral coatings | birnessite | solar energy | redox (bio)geochemistry I nnumerable previous studies concerning the most critical influences of solar energy on the surface of this planet have mainly focused on its influence on Earth's climate (1), on photosynthesis and associated biological processes (2,3), and on geological and soil processes (4). However, although widely exposed natural minerals on Earth's surface receive solar irradiation over very long time periods, the electronic response of these interactions and how this process also shapes the planet on which we live have rarely received attention.…”
mentioning
confidence: 99%
“…phototrophic | mineral coatings | birnessite | solar energy | redox (bio)geochemistry I nnumerable previous studies concerning the most critical influences of solar energy on the surface of this planet have mainly focused on its influence on Earth's climate (1), on photosynthesis and associated biological processes (2,3), and on geological and soil processes (4). However, although widely exposed natural minerals on Earth's surface receive solar irradiation over very long time periods, the electronic response of these interactions and how this process also shapes the planet on which we live have rarely received attention.…”
mentioning
confidence: 99%
“…Analyzing the Mössbauer spectroscopy data, Bogart et al [ 27 ] proposed the following mechanism of transformation of Fe 3 O 4 to γ-Fe 2 O 3 due to the release of Fe-ions from the particles: Fe 2+ are drawn from the nucleus by a concentration gradient arising due to surface oxidation; Fe 2+ is oxidized in situ, colliding with mobile electrons, then Fe 3+ ions are distributed to maintain the electroneutrality of the material. Dissolution of the solid phase and an increase in dissolved Fe 2+ and/or Fe 3+ as a result of incubation of NPs with humic substances was demonstrated by Sundman et al [ 25 ]: the magnetite incubated with native humic substances became more oxidized as compared with the control, i.e., bare magnetite.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown that humic acids (HA) have a high affinity to Fe 3 O 4 NPs and the sorption of HA on the Fe 3 O 4 NP enhanced the stability of Fe 3 O 4 nanodispersions by preventing their aggregation via electrostatic and steric effects [ 19 , 20 , 21 , 22 , 23 ]. However, weak Coulombic attraction, hydrogen, and hydrophobic (van der Waals, π-π, CH-π) bonds between Fe 3 O 4 and HA [ 24 ] seemed not to protect Fe 3 O 4 NPs from the oxidation in real environmental conditions [ 25 , 26 ]. Thus, redox-active HS play an important role in Fe redox speciation in magnetite and can influence their reactivity and role in biogeochemical Fe cycling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This input of energy is known to influence soil properties and development (Carter & Ciolkosz, 1991;Franzmeier et al, 1969;Rech et al, 2001). In addition to thermal energy, the Sun delivers visible and ultraviolet radiation (hereafter referred to as light), which is strong enough to effect discrete chemical reactions among many naturally occurring substances (Doane, 2017), but is rarely investigated past the plant canopy into soil. Research in environmental photochemistry does occasionally involve soil, but this work almost always focuses on the degradation of synthetic soil-borne contaminants (e.g., Frank et al, 2002;Gonçalves et al, 2006;Helz et al, 1994;Katagi, 2004;Marques et al, 2016;Miller & Donaldson, 1994;Zhang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%